Modeling and Analyzing for the Friction Torque of a Sliding Bearing Based on Grey System Theory - Wang Baoming; Xu Jinxin; Chen ShengSheng; Wu Zaixin (Institute of Advanced Engineering and Science, 2014)
Based on the grey system theory, the grey relational analysis method is proposed and used in analyzing the influence of various factors on the friction torque of a sliding bearing. On the basis of the grey relational analysis the multidimensional grey model GM(1,N,D) for the friction torque of a sliding bearing is built up. Taking Al-based alloy sliding bearing as an example, the calculation results show that, compared with other influence factors, friction coefficient, load, temperature and rotational speed have more significant influence on the bearing friction torque.Comparingexperimental results and the calculated value of the GM(1,N,D) model based on these important influence factors, the maximum relative residuals is 9.09%, the average relative residuals is 7.9% and the accuracy is 92.1%. It verify that GM(1,N,D) model has good accuracy and is applicable for predicting friction torque of a sliding bearing.